2014
DOI: 10.1063/1.4881614
|View full text |Cite
|
Sign up to set email alerts
|

Bi-O covalency in PbTiO3-BiInO3 with enhanced ferroelectric properties: Synchrotron radiation diffraction and first-principles study

Abstract: High-TC ferroelectric (1 − x)PbTiO3-xBiInO3 shows a sustainable spontaneous polarization in tetragonal phase by amount of BiInO3 augmented. It is rare and interesting that weak ferroelectric In3+ substitution does not reduce ferroelectricity as most of BiMeO3 materials. To understand this abnormality behavior, the structure and the cation displacements are studied by means of synchrotron radiation diffraction. The cation displacements of A-site atoms and B-site atoms exhibit a coupling property. Their sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…In addition, examining the PbTiO 3 partial DOS in detail, the top of the valence band contains stronger admixtures of Pb s and O p orbitals in comparison to PCBT-60, PSBT-60, and PSCT-60 partial DOS; this represents a stronger PbeO covalency, which in turn stabilizes the larger ferroelectric tetragonal phase in the PbTiO 3 prototype. This observation is consistent with many simulation results reported in the literature [34,35]. From the calculated DOS for PCBT-60, PSBT-60, and PSCT-60 electronic structures, it can be observed that for all three compounds the VB is predominantly composed of O p states, whereas Ti d states contribute predominantly to the CB, as seen Fig.…”
Section: Resultssupporting
confidence: 91%
“…In addition, examining the PbTiO 3 partial DOS in detail, the top of the valence band contains stronger admixtures of Pb s and O p orbitals in comparison to PCBT-60, PSBT-60, and PSCT-60 partial DOS; this represents a stronger PbeO covalency, which in turn stabilizes the larger ferroelectric tetragonal phase in the PbTiO 3 prototype. This observation is consistent with many simulation results reported in the literature [34,35]. From the calculated DOS for PCBT-60, PSBT-60, and PSCT-60 electronic structures, it can be observed that for all three compounds the VB is predominantly composed of O p states, whereas Ti d states contribute predominantly to the CB, as seen Fig.…”
Section: Resultssupporting
confidence: 91%
“…The short‐range disorder dominates in the end. In BS– x BPZnT ceramics, Pb ions at the A‐sites are replaced by Bi ions, which increases the A–O ion hybridization 25 and affects the substitution of B‐site ions (Ti 4+ , Sc 3+ , Zn 2+ ). The Zn‐replaced Ti simultaneously generates O vacancies for electric neutrality.…”
Section: Resultsmentioning
confidence: 99%
“…However, the case of M = In is particularly unusual, since In 3 + ions are weak ferroelectric ions. In the work of Wang and collaborators, [52] they calculated the valence electron density distribution, using density-functional theory, and found that the bismuth-substitution in BiInO 3 À PbTiO 3 systems promotes the covalency between the A-site cations and oxygen atoms, whereas the indium-substitution demotes the covalency between the B-site cations and oxygen atoms. Further calculations of the electron localization function and Bader analysis confirmed that the atomic Bader charges are significantly smaller than the formal ionic charges.…”
Section: Bicoomentioning
confidence: 99%